Damaging Behavior of Masonry Arch Bridges: Analysis of 'Ponte delle Torri' in Spoleto, Italy. Issue 1 (2nd January 2022) - Addessi, Daniela; Liberatore, Domenico; Nocera, Mariacarla
ABSTRACT: Damage effects on the dynamic response of the masonry bridge 'Ponte delle Torri' in Spoleto are investigated. To model ancient masonry material response, a scalar damage variable is introduced in the stress-strain law, whose evolution is driven by a nonlocal strain measure. A 3D finite element formulation is used. Bridge natural frequencies and modal shapes are evaluated and compared with experimental results. Then, the nonlinear step-by-step dynamic analysis of the entire bridge and an equivalent pier is performed, considering a set of natural earthquakes. The response of the bridge is analyzed in terms of top displacement, acceleration and damage patterns.